Peran Hukum Keluarga dalam Menghadapi Tantangan Poligami dalam Masyarakat Kontemporer - Muhammad Husni Abdulah Pakarti; Sofyan Mei Utama; Diana Farid; Hendriana (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Backgound. Polygamy has long been a matter of debate in society, especially in the increasingly complex and globalized contemporary society. In this context, the role of family law becomes very important to face the challenges of polygamy and maintain a balance between traditional values and broader social developments. Aim. The purpose of this study is to determine the extent of the Role of Family Law in Facing the Challenges of Polygamy in Contemporary Society. Methods. The research method used is library research or literature review, this research uses data such as books, journals and other literature obtained from previous studies. after the data is obtained, descriptive analysis is carried out to describe the findings clearly. Results. The results show that the role of family law is very important in facing the challenges of polygamy in contemporary society. The law, MUI fatwa, religious views, women's human rights, and multiculturalism approaches can be a reference in minimizing the negative impact of polygamy practices and maintaining justice and equality between husband and wife.